Circumstances that limit the expansion of ICT (Docentes 2.0 Journal, 2013)
Information and Communication Technologies (ICT) are part of the technological culture that surrounds us and with which we must live. They expand our physical and mental capacities, and the possibilities of social development. The ICT concept includes not only information technology and its associated technologies, telematics and multimedia, but also the media of all kinds: social media ("more media") and traditional interpersonal media with technological support Like the phone, fax.
Keywords: Circumstances; expansion; ICT